(untitled) (Global Journal of Human-Social Science, 2023)
This article aims to verify the relationship of society with nature and its thermodynamic energy flows as an evolutionary element generating totalization and being analyzed by the arrow s of space-time This article will also verify how this process influences the formation of the Anthropocene In this sense the principles born after the advent of quantum mechanics will be applied to the spatial-temporal analysis of physis which integrates society-nature The article also verifies how each formcontent in a unique way contributes energetically to the development of its arrow of space-time Thus it will also be verified as the current production process is associated in general with the disruption of the states of homeotase in the energetic balance of the process of exchange between energy and matter and as the old pattern of relative stability which characterized the Holocene has been replaced by disorder which is at the basis of the emergence of the Anthropocene